A case of spontaneous non-penetrating keratoprosthesis during multi-stage implantation of a Fedorov — Zuyev prosthesis in a patient with a severe chemical eye burn - P. V. Makarov; A. O. Petrova; E. V. Chentsova; O. G. Oganesyan; Y. А. Serov; K. V. Lugovkina (Российский офтальмологический журнал, 2021)
Purpose: to evaluate the results of spontaneous non-penetrating keratoprosthesis with a Fedorov — Zuev prosthesis in a patient with severe chemical burns in both eyes. Material and methods.Patient K., 38, who had sustained a severe burn injury in the past and numerous reconstructive plastic operations on both eyes (amniotic tissue implantation, allolymbal transplantation, layer-by-layer and penetrative keratoplasty, cataract extraction with IOL implantation, total auto-conjunctival corneal plastic surgery) with no functional effect, was subjected to a multi-stage keratoprosthesis of the left eye according to the method practiced by the Helmholtz National Medical Research Center of Eye Diseases. Results.After one of the stages (implantation of the haptic part of the keratoprosthesis with a temporary cylindrical plug), an aseptic necrosis of the tissue above the cylinder occurred. As a result, an unexpected functional effect was revealed: visual acuity of the operated eye 0.02 sph -20.0 D = 0.2. During a dynamic follow-up that lasts 2.5 years, visual acuity remains stable, and the corneallayers behind the cylinder retain transparency. During this time, all stages of keratoprosthesis were performed on the fellow eye with a functional result of 1.0. Conclusion. The long-term result of spontaneous non-penetrating keratoprosthesis indicates the need to study the prospects and develop a method of non-penetrating keratoprosthesis with a Fedorov — Zuyev prosthesis.